Do Shareholder Tender Agreements inform or expropriate shareholders? - Bargeron, Leonce L. (Journal of Corporate Finance, 2012)
By signing a Shareholder Tender Agreement (STA) a shareholder pre-commits to tender her shares to a particular bidder, forsaking the right to tender to any subsequent bidder. In a representative sample of tender offers between 1995 and 2010, 60% of the offers contain an STA. STA deals are associated with lower premiums, greater ownership concentration, greater management ownership, and greater information asymmetry. The results support the hypothesis that STAs certify value to uninformed shareholders, thereby increasing the efficiency of the tender offer process. The evidence does not support the view that STAs expropriate value from shareholders of target companies.